Autism and Refrigerator Mother Theory in Fiction: Pauline Holdstock’s Here I Am! - Alper Tulgar (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Disability studies, in the beginning, focused on the visibility of impairments, and autistic characters, who do not show any visible symptoms, were disregarded. A multidisciplinary approach has recently resulted in integrating autism into humanities. Autism needs to be studied extensively in literary works since unjust representation is a major factor that causes neurotypicals to have fixed and prejudiced ideas about autistic individuals. Scientific studies, in the past, shaped and redefined people’s perceptions of autism. The term ‘refrigerator mother’, popularized by Bruno Bettelheim, was mentioned in Leo Kanner’s account of autism in 1943. The lack of motherliness was considered to be the cause of autism, which formed damaging clichés about autistic children’s mothers. Guilt-ridden mothers blamed themselves for their children’s autism. Autism, an inseparable identity, was treated as a negative effect of bad parenthood. Literary works, especially novels, may maintain or eradicate unjust perceptions of autistic children and their parents. This unfounded hypothesis called ‘refrigerator mother theory’ is not sustained today; however, in the past, it damaged the relationships between autistic children and their mothers. Popular opinion was convinced that mothers were to be blamed for autism. This study aims to discuss the relationship between an autistic child and his mother in the novel Here I Am! by Pauline Holdstock, a British-Canadian writer. It is clear that this unfounded hypothesis is not supported and reflected in the selected novel since the author offers the reader an intimate mother and son relationship in the novel which is in contrast with the typical cold and aloof mother with high intelligence and a needy child.